(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: The need for accumulated dental treatments added to the lack of patient cooperation are the main reasons that lead people with disabilities to need dental care under general anesthesia. Objective: To know the caregiver’s perception of patients with disabilities about the need for dental treatment under general anesthesia. Methods: Qualitative study qualitative. Data were collected between April and July 2017 through semi-structured interviews. Results: Participated in 12 caregivers from nine patients with disability, the age ranged from 25 to 73 years and the average income of 2.5 minimum wages. The dental procedure is perceived as a solving of problems for the patient that refers to the functional scope (chewing and feeding), aesthetics (issues relating to social inclusion), and in terms of relieving physical pain. In addition, the dental procedure is also perceived as a solution to problems for the families, as the needs of patients directly reflect on the life of the family caregiver and other family members, who are in charge of the care and are concerned with solving the dental problems that they harm the patient, interfering with the family routine. Conclusion: Caregivers perceive the dental procedure under general anesthesia as a solution to functional, aesthetic, and physical pain problems for the disabled person. Furthermore, it is perceived as a solution to problems for the family, as it is concerned with the patient’s well-being and understands care as an obligation with a direct impact on family dynamics.